أثر التنفس على جودة الحياة للأفراد بالمملكة العربية السعودية باستخدام طريقة مناي - العنزي، خلف (مؤسسة أكاديميا جلوب للبحث العلمي والنشر الدولي, 2023)
هدف البحث إلى التعرف على أثر التنفس باستخدام طريقة مناي على جودة الحياة للأفراد بالمملكة العربية السعودية، وتمثلت العينة في عدد (20) من المترددين على مركز تنوير للاستشارات والتوجيه، واستخدمت الباحثة المنهج التجريبي، الذي يوفر أوصافا دقيقة للظاهرة محل الدراسة، واستخدمت أدوات: مقياس جودة الحياة، وطريقة مناي باستخدام جلسات التنفس. وتوصل البحث إلى النتائج التالية: - توجد فروق ذات دلالة إحصائية عند مستوى (α = 0.05) بين متوسطات الأفراد في المجموعة التجريبية التي تدربت على طريقة مناي باستخدام جلسات التنفس ومتوسطات الأفراد في المجموعة الضابطة على مقياس جودة الحياة في القياس البعدي. - وجود فروق ذات دلالة إحصائية عند مستوى الدلالة الإحصائية (0.05) في جودة الحياة لدى أفراد العينة تعزى لمتغير: المؤهل العلمي، ونوع العمل، في حين توجد فروق ذات دلالة إحصائية عند مستوى الدلالة الإحصائية (0.05) في جودة لدى أفراد العينة تعزى لمتغير الحالة الاجتماعية لصالح فئة (عزباء). The aim of the research is to apply a demonstration of the use of the method of using the method of applying the method of applying the method of applying the method of applying the method of demonstrating the use of a ruler, use a serial instruction, used it and used it in applying the method of using a training program to be used in applying the curriculum: scale: measure of quality of life, and method Monay uses breathing sessions. The research reached the following results: - There are statistically significant differences at the level of (0.05) between the averages of the individuals in the experimental group that were trained on the method of Moonay using breathing sessions and the averages of the individuals in the control group on the quality- of- life scale in the post-measurement. - There are statistically significant differences at the level of statistical significance (0.05) in the quality of life among the respondents due to the variable: educational qualification and type of work, while there are statistically significant differences at the level of statistical significance (0.05) in the quality of life among the sample members due to the status variable. social status in favor of the (single) category.
Keywords: الضغوط النفسية -- الكفاءة الذاتية -- علم النفس -- السعودية